Solid air entraining agent suitable for plateau low-pressure area as well as preparation method and application of solid air entraining agent
By cleaning and modifying the rubber powder aggregate, a solid gas induction agent suitable for low-air pressure areas on the plateau is prepared, which solves the application problem of concrete in low-air pressure environments on the plateau and significantly improves the freezing resistance and use of concrete. life.
Patent Information
- Application Number
- CN202411413501.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Under the low-pressure environment of plateau, the formation and stability of bubbles inside concrete are affected. Conventional gas-induced methods are difficult to effectively improve the working performance and frost resistance of concrete, and the interface bonding between rubber powder aggregate and cement matrix is weak, which limits the Its application.
By cleaning the rubber powder aggregate, mixing it with carbon nanotubes and nanozinc oxide, adding a modified solution for ultrasonic treatment and mechanical stirring, followed by drying and heat treatment, a solid gas induction agent suitable for low-pressure areas of the plateau was prepared.
It improves the interface bonding between rubber powder aggregate and cement matrix, improves the compactness and frost resistance of concrete, significantly extends the service life of concrete structures, and reduces maintenance costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a solid air entraining agent suitable for plateau low-pressure areas, and a preparation method and application thereof. Background Art
[0002] Usually, air entraining agents are added to concrete to introduce an appropriate amount of tiny bubbles to improve the workability and durability of concrete. However, the low air pressure in the plateau has a significant impact on the generation and stability of bubbles inside the concrete, making it difficult to predict the characteristic parameters of the pores. Conventional air entrainment methods may not be able to effectively improve the workability and frost resistance of concrete in the low-pressure environment of the plateau.
[0003] As an aggregate, rubber powder has large deformation and energy absorption characteristics during the freeze-thaw process, which can reduce frost heave pressure when the temperature drops and inhibit external moisture intrusion when the temperature rises. Therefore, it is an effective strategy to improve the frost resistance of concrete. However, the inventors found in their research that the interface adhesion between rubber powder aggregate and cement matrix is weak, and the weakness of the interface area limits its application under low pressure on the plateau.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a solid air-entraining agent suitable for plateau low-pressure areas and a preparation method and application thereof, so as to help solve or improve the problem of limited application of rubber powder aggregate in plateau low-pressure environments.
[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for preparing a solid air-entraining agent suitable for plateau low-pressure areas, comprising the following steps: (1) cleaning rubber powder aggregate; (2) mixing the rubber powder aggregate obtained by the treatment of step (1) with carbon nanotubes and nano zinc oxide to obtain a solid mixture; (3) mixing the solid mixture with a modified solution to obtain a mixture; the modified solution contains a silane coupling agent, a titanate coupling agent and an ionic liquid; (4) subjecting the mixture to ultrasonic treatment, and mechanically stirring after the ultrasonic treatment, separating the solid from the liquid, and drying to obtain a modified rubber powder aggregate; (5) subjecting the modified rubber powder aggregate to heat treatment to obtain the solid air-entraining agent suitable for plateau low-pressure areas; the heat treatment temperature is 100-120°C, and the heat treatment time is 1.8-2.1h.
[0007] Preferably, in step (1), when the rubber powder aggregate is cleaned, NaOH solution and HCl solution are used to clean the rubber powder aggregate in sequence; after the HCl solution cleaning is completed, the step of plasma treating the rubber powder aggregate is also included; the particle size of the rubber powder aggregate is at least one of 60-80 mesh, 40-60 mesh and 20-40 mesh.
[0008] Preferably, in step (2), the mass ratio of the rubber powder aggregate, carbon nanotubes and nano zinc oxide is (1-2):(1-2):(0.1-0.5).
[0009] Preferably, in step (3), the ionic liquid is 1-allyl-3-methylimidazole chloride-modified graphene oxide; in the modified solution, the mass ratio of silane coupling agent, titanate coupling agent and ionic liquid is (1-2):(1-2):(0.1-0.5); the mass of the modified solution is 1%-5% of the solid mixture.
[0010] Preferably, in step (4), the ultrasonic treatment time is 20-40 min, and the mechanical stirring time is 10-30 min.
[0011] The present invention also provides a solid air-entraining agent suitable for plateau low-pressure areas, which adopts the following technical scheme: a solid air-entraining agent suitable for plateau low-pressure areas, wherein the solid air-entraining agent suitable for plateau low-pressure areas is prepared by the method described above.
[0012] The present invention also provides an antifreeze concrete, which adopts the following technical solution: an antifreeze concrete, the components of which include the solid air entraining agent suitable for plateau low-pressure areas as described above.
[0013] Preferably, the frost-resistant concrete comprises, by weight: 300-500 parts of cement, 1-150 parts of stone powder, 900-1100 parts of coarse aggregate, 600-800 parts of fine aggregate, 4-6 parts of water reducer, 10-70 parts of the solid air entraining agent suitable for plateau low-pressure areas as described in claim 6, and 150-200 parts of water.
[0014] Preferably, the cement is ordinary silicate cement; the stone powder is dolomite slag stone powder with a specific surface area of 500-700m 2 / kg; the coarse aggregate is a 5-31.5mm continuously graded crushed stone aggregate made from dolomite slag; the fine aggregate is machine-made sand with a fineness modulus between 2.3 and 2.7 made from dolomite slag; the water reducer is a polycarboxylic acid water reducer with a water reduction rate greater than 20%.
[0015] The present invention also provides a method for preparing the antifreeze concrete as described above, which adopts the following technical scheme: the method for preparing the antifreeze concrete as described above comprises the following steps: S1. weighing each raw material according to the proportion, wherein the solid air entraining agent suitable for plateau low-pressure areas is added by an internal mixing method, and is added into the reference concrete according to the principle of a fixed percentage of fine aggregate volume, and the corresponding fine aggregate is replaced by an equal volume; S2. cement, stone powder, fine aggregate, coarse aggregate and the solid air entraining agent suitable for plateau low-pressure areas are mixed, dry-mixed, and then water and a water reducer are added and stirred to obtain the antifreeze concrete.
[0016] Beneficial effects:
[0017] The present invention proposes a method for preparing a solid air-entraining agent suitable for plateau low-pressure areas. By using the method of the present invention to process rubber powder aggregate, the interfacial adhesion between the rubber powder aggregate and the cement matrix is improved, the possibility of interfacial damage is reduced, and then it helps to improve the density of concrete when the solid air-entraining agent is used in concrete and reduce the generation of connected holes.
[0018] The solid air entraining agent suitable for plateau low-pressure areas of the present invention is applied to concrete, which can make the concrete have excellent antifreeze performance, and can significantly improve the service life of concrete structures in plateau low-pressure areas and reduce maintenance costs. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0020] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0021] Aiming at the problem that the existing application of rubber powder aggregate in plateau low-pressure environment is limited, the present invention provides a preparation method of a solid air-entraining agent suitable for plateau low-pressure areas.
[0022] The preparation method of the solid air-entraining agent suitable for plateau low-pressure areas according to the embodiment of the present invention comprises the following steps: (1) cleaning rubber powder aggregate; (2) mixing the rubber powder aggregate obtained by the treatment in step (1) with carbon nanotubes and nano zinc oxide to obtain a solid mixture; (3) mixing the solid mixture with a modified solution to obtain a mixture; the modified solution contains a silane coupling agent, a titanate coupling agent and an ionic liquid; (4) ultrasonically treating the mixture, and mechanically stirring, solid-liquid separation and drying after the ultrasonic treatment to obtain a modified rubber powder aggregate; (5) heat-treating the modified rubber powder aggregate to obtain a solid air-entraining agent suitable for plateau low-pressure areas; the heat treatment temperature is 100-120°C (for example, 100°C, 105°C, 110°C, 115°C or 120°C), and the heat treatment time is 1.8-2.1h. Among them, in step (1), by washing the rubber powder aggregate, it is at least helpful to clean up the inorganic impurities and organic impurities on the surface of the rubber powder aggregate; in step (4), the ultrasonic treatment helps to ensure the uniform distribution of the components contained in the modified solution on the surface of the rubber powder particles; the mechanical stirring after the ultrasonic treatment helps to further improve the uniform distribution of the modified solution and the dispersibility of the carbon nanotubes and nano zinc oxide; the heat treatment in step (5) helps to enhance the binding force between the components of the modified solution and the rubber aggregate.
[0023] Freeze-thaw cycles are the main cause of common damage to concrete in cold regions. In extremely cold environments, temperature changes cause hydrostatic pressure on concrete, leading to the expansion of microcracks and pores, and eventually forming macro cracks and causing surface peeling. The rationality of the bubble structure is an important factor affecting the frost resistance of air-entrained concrete. However, the formation and stability of bubbles inside concrete in plateau low-pressure areas are greatly affected, making it impossible to predict the characteristic parameters of its internal pores, and the normal pressure air entrainment method may not be able to effectively improve the working performance and frost resistance of concrete in plateau low-pressure environments. The solid air-entraining agent suitable for plateau low-pressure areas prepared by the method of the present invention helps to solve the above-mentioned technical problems. Specifically, the solid air-entraining agent prepared by the method of the present invention helps to improve the interfacial adhesion between rubber powder aggregate and cement matrix, reduce the possibility of interfacial damage, and further help to improve the density of concrete when it is used in concrete, and reduce the generation of connected holes; in addition, the solid air-entraining agent suitable for plateau low-pressure areas prepared by the method of the present invention can significantly improve the freeze-thaw resistance of concrete, meet the demand for anti-freeze performance of concrete structures in plateau low-pressure areas, effectively solve the cracking problem caused by freeze-thaw cycles, greatly extend the service life of buildings, and have important practical application value.
[0024] In a preferred embodiment of the method for preparing a solid air entraining agent suitable for plateau low-pressure areas of the present invention, in step (1), when cleaning the rubber powder aggregate, the rubber powder aggregate is cleaned with NaOH solution and HCl solution in sequence; after the HCl solution cleaning is completed, the step of plasma treatment of the rubber powder aggregate is also included; the particle size of the rubber powder aggregate is at least one of 60-80 mesh, 40-60 mesh and 20-40 mesh. Among them, firstly, the surface of the rubber powder aggregate is cleaned with NaOH solution (for example, 5% NaOH solution) to remove inorganic impurities and organic impurities on the surface; then, dilute hydrochloric acid pickling is performed to further remove surface impurities and increase the surface activity and specific surface area of the rubber powder; finally, plasma treatment (plasma is the fourth state of matter, composed of charged particles (such as electrons and ions), which is usually formed under high temperature or strong electric field conditions; plasma treatment refers to the use of a plasma spray gun or reactor to bombard the surface of the material with high-energy particles to change the chemical and physical properties of the material) helps to further improve the activity of the surface of the rubber powder aggregate and helps to enhance the adhesion of the subsequent modified material.
[0025] Preferably, during plasma treatment, a plasma device with an argon atmosphere is used to perform plasma treatment on the rubber powder aggregate for a treatment time of 5-10 minutes (for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes) to further improve the activity of the rubber powder surface and enhance the adhesion of subsequent modified materials.
[0026] In a preferred embodiment of the method for preparing a solid air-entraining agent suitable for plateau low-pressure areas of the present invention, in step (2), the mass ratio of rubber powder aggregate, carbon nanotubes and nano zinc oxide is (1-2):(1-2):(0.1-0.5) (for example, 1:1:0.1, 1:1:0.5, 1:1:0.3, 1:2:0.1, 1:2:0.5, 2:1.5:0.1, 2:1:0.3 or 1.5:1.5:0.3, etc.).
[0027] In a preferred embodiment of the method for preparing a solid air-entraining agent suitable for plateau low-pressure areas of the present invention, in step (3), the ionic liquid is 1-allyl-3-methylimidazole chloride-modified graphene oxide; in the modified solution, the mass ratio of the silane coupling agent, the titanate coupling agent and the ionic liquid is (1-2):(1-2):(0.1-0.5) (for example, 1:1:0.1, 1:1:0.5, 1:1:0.3, 1:2:0.1, 1:2:0.5, 2:1.5:0.1, 2:1:0.3, 1.5:1:0.5 or 1.5:2:0.3, etc.); the mass of the modified solution is 1%-5% of the solid mixture (for example, 1%, 2%, 3%, 4% or 5%).
[0028] In a preferred embodiment of the method for preparing a solid air-entraining agent suitable for plateau low-pressure areas of the present invention, in step (4), the time of ultrasonic treatment is 20-40 min (for example, 20 min, 25 min, 30 min, 35 min or 40 min), and the time of mechanical stirring is 10-30 min (for example, 10 min, 15 min, 20 min, 25 min or 30 min).
[0029] The present invention further proposes a solid air-entraining agent suitable for plateau low-pressure areas. The solid air-entraining agent suitable for plateau low-pressure areas in the embodiment of the present invention is prepared by the method described above.
[0030] The present invention further provides an antifreeze concrete. The components of the antifreeze concrete in the embodiment of the present invention include the solid air entraining agent suitable for plateau low-pressure areas as described above.
[0031] In a preferred embodiment of the antifreeze concrete of the embodiment of the present invention, the antifreeze concrete comprises, by weight: 300-500 parts of cement (for example, 300 parts, 350 parts, 400 parts, 450 parts or 500 parts), 1-150 parts of stone powder (for example, 1 part, 10 parts, 40 parts, 70 parts, 110 parts or 150 parts), 900-1100 parts of coarse aggregate (for example, 900 parts, 950 parts, 1000 parts, 1050 parts or 1100 parts), fine aggregate. 600-800 parts (for example, 600 parts, 650 parts, 700 parts, 750 parts or 800 parts), 4-6 parts (for example, 4 parts, 5 parts or 6 parts) of water reducer, 10-70 parts (for example, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts or 70 parts) of solid air entraining agent suitable for plateau low pressure areas as described above, and 150-200 parts (for example, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts or 200 parts) of water.
[0032] The present invention develops antifreeze concrete suitable for plateau low-pressure areas by using stone powder, fine aggregate and coarse aggregate prepared by using cave slag, and by adding the solid air-entraining agent suitable for plateau low-pressure areas of the present invention. The introduction of nanomaterials in the solid air-entraining agent enhances the crack resistance, wear resistance and UV resistance of the concrete, and prolongs the service life of the structure. The solid air-entraining agent shows excellent stability and adaptability in the plateau low-pressure environment; the deformation and energy absorption characteristics of the solid air-entraining agent can be used to ensure the reliability of the antifreeze concrete in the plateau low-pressure environment, providing a longer service life for bridge buildings in plateau low-pressure areas.
[0033] In a preferred embodiment of the antifreeze concrete of the present invention, the cement is ordinary Portland cement; the stone powder is dolomite slag stone powder with a specific surface area of 500-700m 2 / kg (e.g., 500m2 / kg, 550m 2 / kg、600m 2 / kg, 650m 2 / kg or 700m 2 / kg); the coarse aggregate is a crushed stone aggregate with a continuous grade of 5-31.5 mm made from dolomite slag; the fine aggregate is machine-made sand with a fineness modulus between 2.3 and 2.7 made from dolomite slag; and the water reducer is a polycarboxylate water reducer with a water reduction rate greater than 20%.
[0034] The present invention also proposes a method for preparing the concrete as described above. The method for preparing the antifreeze concrete of the embodiment of the present invention comprises the following steps: S1. Weigh each raw material according to the proportion, wherein the solid air entraining agent suitable for plateau low-pressure areas is added by internal mixing method, and is added into the reference concrete according to the principle of fixed percentage of fine aggregate volume, and the corresponding fine aggregate is replaced by equal volume; S2. Cement, stone powder, fine aggregate, coarse aggregate and solid air entraining agent are mixed, dry mixed (mixed evenly), and then water and water reducer are added, and stirred (stirred evenly) to obtain antifreeze concrete. Among them, when cement, stone powder, fine aggregate, coarse aggregate and solid air entraining agent are mixed, the dry mixing time can be 3-4 minutes; after adding water and water reducer, the stirring time can be 4-6 minutes.
[0035] The solid air-entraining agent suitable for plateau low-pressure areas and its preparation method and application are described in detail below through specific embodiments.
[0036] In the following examples, the cement is P·O 525 ordinary Portland cement; the stone powder is dolomite slag stone powder with a specific surface area of 620m 2 / kg; the coarse aggregate is a 5-31.5mm continuously graded crushed stone aggregate made from dolomite slag; the fine aggregate is an artificial sand with a fineness modulus between 2.3 and 2.7 made from dolomite slag; the water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction rate greater than 20%; the carbon nanotubes are multi-walled carbon nanotubes (MWCNTs); the particle size of nano zinc oxide is 20-50nm, and the purity is ≥99%; the silane coupling agent is KH-570; the titanate coupling agent is NDZ-201; and the ionic liquid is 1-allyl-3-methylimidazole chloride modified graphene oxide.
[0037] Example 1
[0038] The preparation method of the solid air-entraining agent suitable for plateau low-pressure areas in this embodiment comprises the following steps:
[0039] (1) First, 5% NaOH solution was used to treat rubber powder aggregate (60-80 mesh, apparent density 1000-1100 kg / m 3) surface is cleaned to remove inorganic and organic impurities on the surface, and then pickled with dilute hydrochloric acid to further remove surface impurities and increase the surface activity and specific surface area of the rubber powder aggregate. Finally, the rubber powder aggregate is plasma treated with an argon atmosphere plasma device (the gas type is argon, the gas flow rate is 150 ml / min, the vacuum degree is 80 Pa, and the radio frequency power is 120 W) for 7 minutes to further improve the activity of the rubber powder surface and enhance the adhesion of subsequent modified materials.
[0040] (2) The rubber powder aggregate, carbon nanotubes and nano zinc oxide are uniformly mixed in a ratio of 1:1:0.2, and then a modified solution composed of a silane coupling agent, a titanate coupling agent and an ionic liquid with a mass fraction of 2% of the rubber powder aggregate is added (wherein the silane coupling agent is KH570, the ionic liquid is 1-allyl-3-methylimidazole chloride-modified graphene oxide, and the mass ratio of the silane coupling agent, the titanate coupling agent and the ionic liquid is 1:1:0.2).
[0041] (3) The mixture was ultrasonically treated for 30 min to ensure uniform distribution of the modifier on the surface of the rubber powder aggregate.
[0042] (4) After the ultrasonic treatment, mechanical stirring was performed for 20 min to further improve the uniform distribution of the modifier and the dispersibility of the nanomaterials.
[0043] (5) The rubber powder aggregate after stirring is naturally air-dried, and then the modified rubber powder aggregate is heat-treated at 100° C. for 2 hours to enhance the bonding force between the modifier and the surface of the rubber powder; after the heat treatment, the solid air-entraining agent of this embodiment suitable for plateau low-pressure areas is obtained.
[0044] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 16 parts of solid air entraining agent suitable for plateau low-pressure areas of this embodiment, and 200 parts of water.
[0045] The preparation method of the antifreeze concrete of the present embodiment comprises the following steps: S1. weighing various raw materials according to the proportion, wherein the amount of rubber powder aggregate used for preparing the solid air entraining agent of the present embodiment is determined by the internal mixing method, the amount of the solid air entraining agent is determined according to the principle of a fixed percentage of the volume of fine aggregate (replacing the corresponding fine aggregate with equal volume), and the solid air entraining agent is mixed into the reference concrete; S2. mixing cement, stone powder, fine aggregate, coarse aggregate and the solid air entraining agent of the present embodiment, dry mixing for 3-4 minutes, then adding water and a water reducing agent, and stirring for 5-8 minutes, so as to obtain the antifreeze concrete of the present embodiment.
[0046] Example 2
[0047] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 720 parts of fine aggregate, 5 parts of water reducer, 33 parts of solid air entraining agent, and 200 parts of water.
[0048] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 10% of the fine aggregate by volume.
[0049] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 60-80 mesh, and the apparent density is 1000-1100 kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0050] Example 3
[0051] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 680 parts of fine aggregate, 5 parts of water reducer, 50 parts of solid air entraining agent, and 200 parts of water.
[0052] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 15% of the fine aggregate by volume.
[0053] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 60-80 mesh, and the apparent density is 1000-1100 kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0054] Example 4
[0055] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 640 parts of fine aggregate, 5 parts of water reducer, 66 parts of solid air entraining agent, and 200 parts of water.
[0056] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 20% of the fine aggregate by volume.
[0057] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 60-80 mesh, and the apparent density is 1000-1100 kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0058] Example 5
[0059] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 15 parts of 40-60 mesh solid air entraining agent, and 200 parts of water.
[0060] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 5% of the fine aggregate by volume.
[0061] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 40-60 mesh, and the apparent density is 900-1000kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0062] Example 6
[0063] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 720 parts of fine aggregate, 5 parts of water reducer, 30 parts of solid air entraining agent, and 200 parts of water.
[0064] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 10% of the fine aggregate by volume.
[0065] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 40-60 mesh, and the apparent density is 900-1000kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0066] Example 7
[0067] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 680 parts of fine aggregate, 5 parts of water reducer, 45 parts of solid air entraining agent, and 200 parts of water.
[0068] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 15% of the fine aggregate by volume.
[0069] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 40-60 mesh, and the apparent density is 900-1000kg / m3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0070] Example 8
[0071] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 640 parts of fine aggregate, 5 parts of water reducer, 60 parts of solid air entraining agent, and 200 parts of water.
[0072] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 20% of the fine aggregate by volume.
[0073] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 40-60 mesh, and the apparent density is 900-1000kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0074] Example 9
[0075] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 14 parts of solid air entraining agent, and 200 parts of water.
[0076] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 5% of the fine aggregate by volume.
[0077] The solid air entraining agent of this embodiment is suitable for plateau low pressure areas (the particle size of the rubber powder aggregate used to prepare the solid air entraining agent is 20-40 mesh, and the apparent density is 800-900 kg / m 3 ) and the preparation method of frost-resistant concrete are the same as in Example 1.
[0078] Example 10
[0079] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 720 parts of fine aggregate, 5 parts of water reducer, 27 parts of solid air entraining agent, and 200 parts of water.
[0080] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 10% of the fine aggregate by volume.
[0081] The preparation method of the solid air-entraining agent (the rubber powder aggregate used to prepare the solid air-entraining agent has a particle size of 20-40 mesh and an apparent density of 800-900 kg / m3) and frost-resistant concrete suitable for plateau low-pressure areas in this embodiment is the same as that in Example 1.
[0082] Embodiment 11
[0083] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 680 parts of fine aggregate, 5 parts of water reducer, 41 parts of solid air entraining agent, and 200 parts of water.
[0084] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 15% of the fine aggregate by volume.
[0085] The preparation method of the solid air-entraining agent (the rubber powder aggregate used to prepare the solid air-entraining agent has a particle size of 20-40 mesh and an apparent density of 800-900 kg / m3) and frost-resistant concrete suitable for plateau low-pressure areas in this embodiment is the same as that in Example 1.
[0086] Example 12
[0087] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 640 parts of fine aggregate, 5 parts of water reducer, 54 parts of solid air entraining agent, and 200 parts of water.
[0088] Among them, the addition of stone powder and solid air entraining agent adopts the internal mixing method. In terms of mass percentage, the stone powder replaces 20% of the cement by mass; in terms of volume percentage, the solid air entraining agent replaces 20% of the fine aggregate by volume.
[0089] The preparation method of the solid air-entraining agent (the rubber powder aggregate used to prepare the solid air-entraining agent has a particle size of 20-40 mesh and an apparent density of 800-900 kg / m3) and frost-resistant concrete suitable for plateau low-pressure areas in this embodiment is the same as that in Example 1.
[0090] Example 13
[0091] The frost-resistant concrete of this embodiment is different from that of Embodiment 1 in that the rubber micro-aggregate used to prepare the solid air-entraining agent includes 60-80 mesh rubber powder aggregate, 40-60 mesh rubber powder aggregate and 20-40 mesh rubber powder aggregate, and the mass ratio of the three is 1:1:1.
[0092] The frost-resistant concrete of this embodiment includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 680 parts of fine aggregate, 5 parts of water reducer, 16 parts of solid air entraining agent, and 200 parts of water.
[0093] Comparative Example 1
[0094] The frost-resistant concrete of this comparative example is different from that of Example 1 only in that the solid air-entraining agent is replaced by a liquid air-entraining agent.
[0095] The frost-resistant concrete of this comparative example includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 2 parts of liquid air entraining agent, and 200 parts of water.
[0096] The method for preparing the frost-resistant concrete of this comparative example comprises the following steps: S1. weighing each raw material according to the proportion;
[0097] S2. Mix cement, stone powder, fine aggregate and coarse aggregate, dry mix for 3-4 minutes, then add water, water reducing agent and liquid air entraining agent, and stir for 5-8 minutes.
[0098] Comparative Example 2
[0099] The frost-resistant concrete of this comparative example is different from that of Example 1 in that the stone powder is replaced by cement of equal mass, and the solid air-entraining agent is replaced by a liquid air-entraining agent.
[0100] The frost-resistant concrete of this comparative example includes the following raw materials in parts by weight: 500 parts of cement, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 2 parts of liquid air entraining agent, and 200 parts of water.
[0101] Comparative Example 3
[0102] The frost-resistant concrete of this comparative example is different from that of Example 1 in that the stone powder is replaced with cement of equal mass.
[0103] The frost-resistant concrete of this comparative example includes the following raw materials in parts by weight: 500 parts of cement, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducer, 16 parts of solid air entraining agent, and 200 parts of water.
[0104] Comparative Example 4
[0105] The frost-resistant concrete of this comparative example is different from that of Example 1 in that the solid air-entraining agent is unmodified rubber powder aggregate.
[0106] The concrete of this comparative example includes the following raw materials in parts by weight: 500 parts of cement, 1000 parts of coarse aggregate, 760 parts of fine aggregate, 5 parts of water reducing agent, 16 parts of 60-80 mesh rubber powder aggregate (unmodified), and 200 parts of water.
[0107] Comparative Example 5
[0108] The difference between the frost-resistant concrete of this comparative example and Example 1 is that the solid air-entraining agent is omitted and the amount of fine aggregate is 780 parts; the rest is the same as Example 1;
[0109] The frost-resistant concrete of this comparative example includes the following raw materials in parts by weight: 400 parts of cement, 100 parts of stone powder, 1000 parts of coarse aggregate, 780 parts of fine aggregate, 5 parts of water reducing agent, and 200 parts of water.
[0110] Comparative Example 6
[0111] The difference between this comparative example and Example 1 is that nano zinc oxide is omitted when preparing the solid air-entraining agent; the rest is consistent with Example 1.
[0112] Comparative Example 7
[0113] The difference between this comparative example and Example 1 is that the carbon nanotubes are omitted when preparing the solid air-entraining agent; the rest is consistent with Example 1.
[0114] Comparative Example 8
[0115] The difference between this comparative example and Example 1 is that the silane coupling agent is omitted when preparing the solid air entraining agent; the rest is consistent with Example 1.
[0116] Comparative Example 9
[0117] The difference between this comparative example and Example 1 is that the titanate coupling agent is omitted when preparing the solid air-entraining agent; the rest is consistent with Example 1.
[0118] Comparative Example 10
[0119] The difference between this comparative example and Example 1 is that the ionic liquid is omitted when preparing the modified rubber (the ionic liquid is replaced by an equal amount of ethanol); the rest is consistent with Example 1.
[0120] Comparative Example 11
[0121] The difference between this comparative example and Example 1 is that the step of heat treatment at 100°C is omitted when preparing the solid air-entraining agent (step (4) is to separate the solid after ultrasonic treatment, and dry it to obtain the solid air-entraining agent); the rest is consistent with Example 1.
[0122] Experimental example
[0123] 1. Mechanical properties test:
[0124] According to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081-2019), the compressive strength and splitting tensile strength of concrete are tested before freezing and thawing. Specifically:
[0125] Concrete compressive strength test method:
[0126] Specimen preparation: Standard cube (side length 150mm) or cylinder (diameter 150mm, height 300mm) specimens are usually used. The specimens should be cured under standard curing conditions for up to 28 days;
[0127] Place the specimen on the workbench of the pressure testing machine so that the pressure acts evenly on the pressure-bearing surface of the specimen. Start the testing machine and apply vertical pressure. The loading rate should be uniformly loaded according to the standard (such as 0.6MPa / s) until the specimen is destroyed.
[0128] Concrete splitting tensile strength test method:
[0129] Specimen preparation: Standard cylindrical specimens (diameter 150 mm, height 300 mm) are usually used, and the specimens are also cured under standard curing conditions for 28 days;
[0130] Start the testing machine and apply vertical pressure. The loading rate should be uniformly loaded according to the standard (such as 0.08MPa / s) until the specimen is split and damaged.
[0131] The mechanical properties test results are shown in Table 1 below:
[0132] Table 1
[0133]
[0134] Combining the experimental data of Comparative Example 4 (using rubber powder aggregate as solid air entraining agent) and Comparative Example 5 (no air entraining agent) in Table 1, it can be seen that after adding rubber powder aggregate into concrete, the strength of concrete will decrease; however, combining Example 1 and Comparative Example 4, it can be seen that when the solid air entraining agent prepared by treating rubber powder aggregate in the present invention is added to concrete, the mechanical properties of concrete can be significantly improved, reaching a level basically equivalent to that of Comparative Example 5 (the mechanical properties of Example 13 are even significantly better than those of Comparative Example 5). This shows that the solid air entraining agent of the present invention can improve the mechanical properties of concrete (for example, density, interface bonding performance, etc.) to a certain extent relative to rubber powder aggregate.
[0135] 2. Freeze-thaw resistance test:
[0136] The concrete prepared in the embodiment and the comparative example was tested for freeze-thaw resistance. The test method was based on ASTM / C666 "Standard Test Method for Rapid Freezing-Thawing Capacity of Concrete". The duration of a freeze-thaw cycle was about 3 hours. The time for thawing was not less than 0.5 hours. The center temperatures of the specimens during freezing and thawing were (-18±2)°C and (5±2)°C, respectively. The number of freeze-thaw cycles was 300.
[0137] Use special low-pressure simulation equipment to adjust the air pressure, temperature and humidity in the test chamber to simulate the actual environmental conditions in high-altitude low-pressure areas. During the low-pressure test, the air pressure in the test chamber is ~70kPa; during the normal pressure test, the air pressure is ~101kPa.
[0138] The mass loss rate and relative elastic modulus test results of the frost-resistant concrete of the embodiment and the comparative example after freeze-thaw cycles are shown in Table 2 below:
[0139] Table 2
[0140]
[0141] It can be seen from Table 1-2 that the solid air-entraining agent prepared by the present invention and suitable for plateau low-pressure areas has effectively improved the antifreeze performance of concrete on the basis of ensuring its mechanical properties.
[0142] Among them, from the comparison of Examples 1 to 12, it can be seen that with the increase of the solid air entraining agent dosage, the mass loss of concrete first decreases and then increases, and the relative dynamic elastic modulus first increases and then decreases. When the dosage is 15%, the antifreeze performance of concrete reaches the best. In addition, the optimization effect of the solid air entraining agent on the antifreeze performance of concrete increases with the decrease of particle size.
[0143] It can be seen from the comparison between Example 1 and Comparative Example 1 that the solid air-entraining agent prepared by the present invention has a better effect on improving the antifreeze performance of concrete under low pressure than the existing liquid air-entraining agent. The low pressure environment greatly limits the formation and stability of bubbles inside the concrete by the liquid air-entraining agent. However, the solid air-entraining agent will not be significantly affected by the low pressure during the freeze-thaw process. When the stress of the concrete increases due to the freezing and expansion of water, cracks are constantly generated inside and gradually expand into cracks. Since the solid air-entraining agent is an elastomer, it can buffer the expansion pressure and prevent the continued expansion of the internal cracks, so that the concrete can obtain better antifreeze performance. At the same time, the addition of the solid air-entraining agent can improve the internal pore structure, introduce a large number of bubbles, form many closed pores, and inhibit the development of capillary pores formed by cement hydration inside the specimen, thereby effectively improving the antifreeze performance of the concrete.
[0144] From the comparison of Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that when 20% of the stone powder is added, the concrete still has excellent antifreeze performance, and its mass loss rate and relative dynamic elastic modulus in a low pressure environment are not significantly different from those of the pure cement system.
[0145] By comparing Example 1, Comparative Example 1, and Comparative Examples 4-11, it can be seen that the solid air-entraining agent prepared by the present invention has an excellent modification effect on rubber micro-aggregate. When the rubber micro-aggregate is not modified, it is difficult to combine with cement mortar, resulting in poor adhesion between the rubber micro-aggregate and the matrix, forming a relatively weak bonding surface, but at this time, the effect of improving the antifreeze performance of the structure is still better than that of the liquid air-entraining agent. The addition of carbon nanotubes improves the interfacial bonding ability between the rubber micro-aggregate and the matrix, while improving the toughness and crack resistance of the concrete, and reducing the crack expansion caused by freeze-thaw cycles. Nano zinc oxide fills micropores, reduces water infiltration, reduces freeze-thaw damage, and improves the ultraviolet stability of concrete structures in plateau areas. Silane coupling agents improve interfacial bonding and water resistance, and reduce interfacial damage caused by freeze-thaw cycles. Titanate coupling agents reduce interfacial damage and thermal expansion and contraction stress, and improve antifreeze performance. Ionic liquids improve dispersibility and interfacial wettability, and enhance chemical stability. The solid air entraining agent of the present invention not only improves the density of the concrete structure and reduces the formation rate of the interconnected pores, but also improves the interface adhesion between the rubber micro-aggregate and the cement matrix, and reduces the possibility of interface damage. Therefore, relative to ordinary rubber micro-aggregates, the solid air entraining agent of the present invention not only gives full play to its inherent deformation characteristics, but also improves the weakest interface transition zone in the structure composed of the cement matrix and the rubber micro-aggregate, so the antifreeze effect is significantly improved. The change in concrete porosity also verifies this conclusion.
[0146] From the experimental results of freeze-thaw cycle experiments of Example 1, Comparative Example 1 and Comparative Example 5 under normal pressure and low pressure conditions, it can be seen that the solid air-entraining agent prepared by the present invention has a better regulating effect on the antifreeze performance of concrete under the low pressure environment of the plateau. When the traditional liquid air-entraining agent is applied from the ordinary freeze-thaw environment to the low pressure freeze-thaw environment of the plateau, the mass loss rate increases by more than 3%; while the solid air-entraining agent, when applied from the ordinary freeze-thaw environment to the low pressure freeze-thaw environment of the plateau, the mass loss rate increases by less than 1.5%. At the same time, the effect of improving the antifreeze performance of concrete by the solid air-entraining agent under the ordinary freeze-thaw environment is still significantly better than that of the traditional liquid air-entraining agent. In addition, combined with Comparative Example 1 and Comparative Example 5, it can be seen that: the liquid air-entraining agent under normal pressure has a good effect on improving the antifreeze-thaw performance of concrete, but the antifreeze-thaw performance of Comparative Example 1 with the addition of liquid air-entraining agent under low pressure is even worse than that of Comparative Example 5 without the addition of air-entraining agent; this is because the air-entraining agent under low pressure introduces an insufficient number of bubbles in the concrete and the quality is poor (i.e., the size is larger).
[0147] Comprehensive analysis of the effects of solid air-entraining agent particle size and dosage on freeze-thaw resistance shows that the mix ratio of particle size 60-80 mesh: 40-60 mesh: 20-40 mesh = 1:1:1 and dosage 15% (Example 13) is the recommended relatively optimal mix ratio. The solid air-entraining agent prepared on this basis and the antifreeze concrete containing the air-entraining agent can ensure excellent freeze-thaw resistance in plateau low-pressure areas, and can be used to guide the optimization design of the mix ratio of the same type of materials.
[0148] 3. Porosity test before and after freeze-thaw:
[0149] Test method: The water saturation method is a commonly used method to measure the porosity of concrete. The porosity is calculated by completely immersing the concrete test block in water and measuring its weight change. The following is the specific test method:
[0150] (1) Dry the concrete specimen in an oven, usually at 105°C for 24 hours, to ensure that the specimen is completely dry. Record the mass after drying, md;
[0151] (2) Place the dried test piece in water and immerse it completely. The vacuum saturation method is usually used, that is, immersing the test piece in water under vacuum conditions to ensure that all pores are filled with water; the immersion time depends on the specific situation and can be 24 hours or longer, until the weight of the test piece no longer increases;
[0152] (3) Take the test piece out of the water, gently wipe the surface moisture with a cloth, and record the mass ms after water saturation;
[0153] (4) Measure the volume V of the test piece by geometric measurement or displacement method.
[0154] The porosity (P) can be calculated by the following formula: P = (ms-md) / ρo·V×100%;
[0155] Where: P is the porosity (%), md is the mass of the dry specimen (g), ms is the mass of the water-saturated specimen (g), ρo is the density of water, usually 1g / cm3, and V is the volume of the specimen (cm3).
[0156] The specific experimental results are shown in Table 3 below:
[0157] Table 3
[0158] Group Test conditions Porosity before freeze-thaw (%) Porosity after freeze-thaw (%) Example 1 Low pressure 5.71 9.52 Normal pressure 4.98 8.36 Example 2 Low pressure 5.66 9.2 Example 3 Low pressure 5.43 8.42 Example 4 Low pressure 5.9 9.87 Example 5 Low pressure 6.96 13.86 Example 6 Low pressure 7.11 13.21 Example 7 Low pressure 7.26 12.93 Example 8 Low pressure 7.31 13.79 Example 9 Low pressure 8.13 15.66 Example 10 Low pressure 8.26 15.21 Embodiment 11 Low pressure 8.39 14.92 Example 12 Low pressure 8.41 15.57 Example 13 Low pressure 5.21 8.68 Comparative Example 1 Low pressure 7.21 21.74 Normal pressure 6.18 10.69 Comparative Example 2 Low pressure 7.02 18.66 Comparative Example 3 Low pressure 6.03 10.22 Comparative Example 4 Low pressure 6.65 11.74 Comparative Example 5 Low pressure 5.63 18.92 Normal pressure 4.88 16.8 Comparative Example 6 Low pressure 6.19 11.28 Comparative Example 7 Low pressure 6.27 12.03 Comparative Example 8 Low pressure 6.57 14.29 Comparative Example 9 Low pressure 6.61 15.01 Comparative Example 10 Low pressure 6.29 11.17 Comparative Example 11 Low pressure 6.15 10.99
[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid air-entraining agent suitable for plateau low-pressure areas, characterized in that: The steps include: (1) Cleaning the rubber powder aggregate; (2) uniformly mixing the rubber powder aggregate obtained by the treatment in step (1) with carbon nanotubes and nano zinc oxide to obtain a solid mixture; (3) mixing the solid mixture with a modified solution to obtain a mixture; the modified solution contains a silane coupling agent, a titanate coupling agent and an ionic liquid; (4) subjecting the mixture to ultrasonic treatment, and after the ultrasonic treatment, mechanically stirring, solid-liquid separation, and drying to obtain modified rubber powder aggregate; (5) The modified rubber powder aggregate is heat-treated to obtain the solid air-entraining agent suitable for plateau low-pressure areas; the heat treatment temperature is 100-120° C., and the heat treatment time is 1.8-2.1 hours.
2. The method for preparing a solid air-entraining agent suitable for plateau low-pressure areas according to claim 1, characterized in that: In step (1), when the rubber powder aggregate is washed, the rubber powder aggregate is washed with a NaOH solution and then with an HCl solution; After the HCl solution cleaning is completed, the step of plasma treating the rubber powder aggregate is also included; The particle size of the rubber powder aggregate is at least one of 60-80 mesh, 40-60 mesh and 20-40 mesh.
3. The method for preparing a solid air-entraining agent suitable for plateau low-pressure areas according to claim 1, characterized in that: In step (2), the mass ratio of the rubber powder aggregate, carbon nanotubes and nano zinc oxide is (1-2):(1-2):(0.1-0.5).
4. The method for preparing a solid air-entraining agent suitable for plateau low-pressure areas according to claim 1, characterized in that: In step (3), the ionic liquid is 1-allyl-3-methylimidazole chloride-modified graphene oxide; In the modified solution, the mass ratio of the silane coupling agent, the titanate coupling agent and the ionic liquid is (1-2):(1-2):(0.1-0.5); The mass of the modified solution is 1%-5% of the solid mixture.
5. The method for preparing a solid air-entraining agent suitable for plateau low-pressure areas according to claim 1, characterized in that: In step (4), the ultrasonic treatment time is 20-40 min, and the mechanical stirring time is 10-30 min.
6. A solid air-entraining agent suitable for plateau low-pressure areas, characterized in that: The solid air-entraining agent suitable for plateau low-pressure areas is prepared by the method described in any one of claims 1 to 5.
7. A frost-resistant concrete, characterized in that: The components of the antifreeze concrete include the solid air entraining agent suitable for plateau low-pressure areas as described in claim 6.
8. The frost-resistant concrete according to claim 7, characterized in that: In parts by weight, the frost-resistant concrete comprises: 300-500 parts of cement, 1-150 parts of stone powder, 900-1100 parts of coarse aggregate, 600-800 parts of fine aggregate, 4-6 parts of water reducer, 10-70 parts of solid air entraining agent suitable for plateau low-pressure areas as claimed in claim 6, and 150-200 parts of water.
9. The frost-resistant concrete according to claim 8, characterized in that: The cement is ordinary Portland cement; The stone powder is dolomite slag powder with a specific surface area of 500-700m 2 / kg; The coarse aggregate is a 5-31.5 mm continuously graded crushed stone aggregate made from dolomite slag; The fine aggregate is machine-made sand with a fineness modulus between 2.3 and 2.7 made from dolomite slag; The water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate greater than 20%.
10. The method for preparing frost-resistant concrete according to claim 8 or 9, characterized in that: The steps include: S1. Weigh the raw materials according to the proportion, wherein the solid air-entraining agent suitable for plateau low-pressure areas is added by internal mixing method, and is added to the reference concrete according to the principle of fixed percentage of fine aggregate volume, and the corresponding fine aggregate is replaced by equal volume; S2. Mix cement, stone powder, fine aggregate, coarse aggregate and the solid air entraining agent suitable for plateau low-pressure areas, dry mix, add water and water reducing agent, stir, and obtain the antifreeze concrete.
Citation Information
Patent Citations
Carbon nanotube reinforced rubber aggregate cement-based material
CN109721267A
Silanized rubber / nano SiO2 composite anti-freezing concrete and preparation method thereof
CN115784684A
Rubber composition for tread and preparation method thereof
CN117777561A
Cited By
Concrete bubble regulating agent suitable for high-altitude areas and preparation method of concrete bubble regulating agent
CN120157379A
A concrete bubble regulating agent suitable for high altitude areas and a preparation method thereof
CN120157379B